Business Sustainability Analysis of Tapis Jejama Kham MSMEs among Youth - Listiana, Indah; Rara,; Gultom, Dame T; Nurmayasari, Indah (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
The declining number of Tapis craftsmen signifies a waning cultural interest. It is imperative to proactively address the imperative of ensuring the continuity of Tapis Micro, Small, and Medium Enterprises (MSMEs) as a means to safeguard Lampung's rich craft heritage in an ever-evolving world. Thus, a comprehensive analysis of the business sustainability of Tapis MSMEs within the younger generation, who serve as both successors and conservators of the Lampung Tapis tradition, becomes a necessity. This study is dedicated to evaluating the status of business continuity within the Tapis Jejama Kham MSME, conducted during September-October 2022 in Negeri Katon, Pesawaran, Lampung, Indonesia. The research engaged 32 respondents, all of whom were members of the Tapis Jejama Kham MSMEs, aged between 16 and 30 years. Employing a quantitative descriptive approach with a focus on the Triple Bottom Line (TBL) methodology, this study elucidates that the economic aspect, driven by the aspirations of the younger generation to enhance their family's standard of living, predominantly underpins the sustainability of this enterprise.